Effects of nurse-led telephone follow-up for discharged patients treated with chemotherapy - Gui Li (Asia-Pacific Journal of Oncology Nursing, 2014)
Objective: Nurse-led telephone follow-up is effective in meeting information and psycho-social needs. We explored the potential effects of nurse-led telephone follow-up for patients treated with chemotherapy in China. Methods: A quasi-experimental study was employed in the research. 300 cases of cancer inpatients in a cancer hospital in Beijing during July-October 2012 were selected by convenience sampling. To compare the satisfaction and response regarding to chemotherapy adverse side effects, patients who discharged on Monday and Friday were provided with telephone follow-up. Patients who discharged on Tuesday, Wednesday and Thursday received routine care. Results: Via telephone follow-up, patient satisfaction relating to nursing care increased. Moreover, their response to chemotherapy adverse side effects showed a significant difference. Conclusion: Telephone follow-up by specialist nurses may be a feasible option. It was well received by patients, with no physical or psychological disadvantage.